The role of supervisory practices for school principals in the professional development of new teachers in the schools of education in the governorates of Hawat Bani Tamim and Al-Hareiq from the point of view of the new principals and teachers - al-Samih, Mohammed bin Ibrahim (Journal of Educational and Psychological Sciences, 2017)
The study aimed at identifying the role of supervising practices for school principals in the professional development of new teachers in the schools of education in Hawat Bani Tamim and Al-Harraq governorates and reaching the most important suggestions and recommendations that may contribute to improving the supervisory practices of school principals to develop new teachers professionally. A descriptive descriptive approach was used and a questionnaire consisting of (44) words was applied in the fields of study divided into three axes. After verifying the validity and validity of the tool, it was applied to the study community consisting of 35 managers and 46 teachers. It was found that the members of the study community fully agree that managers carry out many supervisory practices that contribute to the professional development of new teachers with an average of 4.59 out of 5.00. The members of the study community fully agree on the role of supervisory practices for school principals to achieve the professional development of new teachers, (4.56 out of 5.00). It was found that the members of the study community fully agree on ways to improve the supervisory practices of school principals to achieve the professional development of the new teachers (4.36 out of 5.00). There were no statistically significant differences in the opinions of the study community members And the new teachers on all study axes according to all the variables of the study except the variable nature of work, where the differences came in favor of the members of the study society of the managers.